P‐127: Dual‐Gate Self‐Aligned IGZO TFTs Monolithically Integrated with High‐Temperature Bottom Moisture Barrier for Flexible AMOLED. Issue 1 (30th May 2018) - Kronemeijer, Auke Jisk; Akkerman, Hylke; van der Steen, Jan-Laurens; Steudel, Soeren; Pendyala, Raghu; Panditha, Pradeep; Bel, Thijs; van Diesen, Karin; de Haas, Gerard; Maas, Joris; de Riet, Joris; Rovers, Madelon; et al.
Abstract : We present a 350°C self‐aligned dual‐gate a‐IGZO backplane technology with a monolithically integrated multi‐layer high‐temperature thin‐film barrier for flexible AMOLED. Thin‐film barrier properties and TFT technology are optimized on 320 x 352mm substrates, and demonstrated in a flexible QQVGA 100 ppi AMOLED display prototype.